2010
DOI: 10.1097/tp.0b013e3182000042
|View full text |Cite
|
Sign up to set email alerts
|

Ganciclovir Pharmacokinetic Parameters Do Not Change When Extending Valganciclovir Cytomegalovirus Prophylaxis From 100 to 200 Days

Abstract: The pharmacokinetics of ganciclovir were similar between the two dosing groups (100 vs. 200 days), with the majority of patients achieving an area under the concentration time curve in the target therapeutic range (40-60 μg hr/mL). The fact that the majority of patients were within the target therapeutic range and the absence of a control arm (no treatment) precluded any attempt to validate a correlation with clinical parameters (i.e., CMV disease).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 15 publications
(16 reference statements)
1
24
0
Order By: Relevance
“…Welker et al conducted a PK substudy (n = 120) from a multicentre double‐blind, randomised, placebo‐controlled trial. The clinical trial compared 100 days versus 200 days of 900‐mg ValGCV daily prophylaxis (Valcyte; F Hoffmann‐La Roche Ltd) in 326 CMV D+/R− kidney transplant recipients (Table ) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Welker et al conducted a PK substudy (n = 120) from a multicentre double‐blind, randomised, placebo‐controlled trial. The clinical trial compared 100 days versus 200 days of 900‐mg ValGCV daily prophylaxis (Valcyte; F Hoffmann‐La Roche Ltd) in 326 CMV D+/R− kidney transplant recipients (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest exposures between 40 and 50 μg·h/mL prevent CMV viraemia in this particular population (D+/R−), where the absolute risk of CMV disease is the highest . Interestingly, GCV AUC 0‐24 values below 40 μg·h/mL have been reported in two studies that investigated D+/R− SOT recipients, despite following the manufacturer's dosing algorithm . Furthermore, Padullés et al found 81.5% of SOT recipients (D+/R−, D+/R+, D−/R+, D‐/R−) did not reach GCV exposures between 40 and 50 μg·h/mL when following the manufacturer's dosing algorithm.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The average exposure at time of event was calculated taking the dosing history of the patient into account. The correlation analyses between individual ganciclovir AUC 0–24 and the occurrence of safety adverse events (yes/no) were performed by logistic regression, as described previously …”
Section: Methodsmentioning
confidence: 99%
“…The average exposure at time of event was calculated taking the dosing history of the patient into account. The correlation analyses between individual ganciclovir AUC 0 -24 and the occurrence of safety adverse events (yes/no) were performed by logistic regression, as described previously 2,28. RESULTSValganciclovir dosing algorithms for the prevention of CMV diseaseThe simulated median AUC 0-24 values, together with the fraction of patients within, below, and above the target range of 40-60 μg • hour/mL for each age group after dosing with valganciclovir are summarized inTable 2.…”
mentioning
confidence: 99%